2022
DOI: 10.1177/0271678x221078065
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cerebral hypoperfusion and blood-brain barrier disruption in uninjured brain areas of rhesus monkeys subjected to transient ischemic stroke

Abstract: Blood-brain barrier (BBB) disruption is a pivotal pathophysiological process in ischemic stroke. Although temporal changes in BBB permeability during the acute phase have been widely studied, little is known about the chronic phase of cerebrovascular changes that may have a large impact on the long-term outcome. Therefore, this study was aimed to measure cerebral vascular abnormalities using CT perfusion in nine rhesus monkeys subjected to transient middle cerebral artery occlusion (tMCAO) for ≥1 year (MCAO-1Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…Fluid flow also plays roles in BBB regulation and endothelial glycocalyx‐related gene expressions 62 . Platelet‐derived growth factor B is critical for pericyte coverage and BBB function, 63 while cerebral hypoperfusion, BBB disruption and CSF Aβ decrease are related to long‐term neurological deficits 64 . Just as modulation networks hint, POCD is caused by joint action of multiple CNS cell types under surgical stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluid flow also plays roles in BBB regulation and endothelial glycocalyx‐related gene expressions 62 . Platelet‐derived growth factor B is critical for pericyte coverage and BBB function, 63 while cerebral hypoperfusion, BBB disruption and CSF Aβ decrease are related to long‐term neurological deficits 64 . Just as modulation networks hint, POCD is caused by joint action of multiple CNS cell types under surgical stress.…”
Section: Discussionmentioning
confidence: 99%
“…62 Platelet-derived growth factor B is critical for pericyte coverage and BBB function, 63 while cerebral hypoperfusion, BBB disruption and CSF Aβ decrease are related to long-term neurological deficits. 64 Just as modulation networks hint, POCD is caused by joint action of multiple CNS cell types under surgical stress. The symptoms of POCD include impairments of memory, attention, action and perception, and several DEGs found in the present study (Ncam1, Srf, etc.)…”
Section: Discussionmentioning
confidence: 99%
“… 24 BBB permeability is an important pathophysiological process during the stroke. 25 , 26 At the same time, no intracerebral hemorrhage occurred in the FUS group, but different degrees of cerebral hemorrhage occurred when FUS and μBs are combined in the other two groups. Therefore, the presence of both the appropriate ultrasound field and the μBs are necessary for the hemorrhage to occur.…”
Section: Discussionmentioning
confidence: 87%
“…24 BBB permeability is an important pathophysiological process during the stroke. 25,26 At the same time, no intracerebral hemorrhage occurred in the FUS group, but different degrees of When ICH occurs, the hematoma compresses the surrounding tissue leading to ischemia and hypoxia in the compressed tissue, which causes oxidative stress and oxidative damage in the brain tissue. 27,28 Previous studies have shown that edaravone protects neurons and vascular endothelial cells by scavenging free radicals (such as hydrogen peroxide and hydroxyl radicals) and inhibiting lipid peroxidation.…”
Section: Discussionmentioning
confidence: 97%
“…50 Chronic CBF dysregulation and BBB impairment may change Aβ metabolism and result in a cognitive decline apart from typical vascular dementia. 51 In addition, reparative angiogenesis can reduce white matter lesions and irreversible neuronal injury under chronic hypoperfusion. 52 Previous studies indicate that the occurrence of blood-brain barrier (BBB) leakage is earlier than demyelination, and vascular abnormality may compromise oligodendrogenesis and myelin regeneration in BCAS.…”
Section: Discussionmentioning
confidence: 99%